Pengembangan Media Pembelajaran Berbasis Lembar Kerja Peserta Didik (LKPD) Audiovisual pada Materi Puisi untuk Siswa Kelas X SMA - Lingga, Debi Marlina; Rita, Rita; Soraya, Ratna (Medan Resource Center, 2025)
This study aims to develop an audiovisual-based Student Worksheet (LKPD) as an innovative learning medium for teaching poetry to tenth-grade high school students. The development addresses the limited variety of instructional media and students' low motivation in understanding poetic texts. The research employed a Research and Development (R&D) approach, adapting the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation. Data were collected from tenth-grade students at a high school in Medan City using a needs analysis questionnaire and student learning outcome assessments. The developed audiovisual-based LKPD was validated through expert judgment involving both content and media design experts. Quantitative results showed a high level of validity, with material expert scores reaching 86% and media expert evaluations averaging 71%. These findings suggest that the audiovisual-based LKPD is pedagogically sound and practically feasible for classroom implementation. It offers an engaging alternative for poetry instruction and holds potential for broader application in literature education. The study concludes that integrating audiovisual elements into student worksheets can enhance student engagement and comprehension, making it a viable tool for contemporary language learning environments.